Effects of coronary sinus occlusion on myocardial ischaemia in humans: role of coronary collateral function. Issue 8 (23rd January 2013) - Stoller, Michael; Traupe, Tobias; Khattab, Ahmed A; de Marchi, Stefano F; Steck, Hélène; Seiler, Christian
Abstract : Objective: This study tested the hypotheses that intermittent coronary sinus occlusion (iCSO) reduces myocardial ischaemia, and that the amount of ischaemia reduction is related to coronary collateral function. Design: Prospective case-control study with intraindividual comparison of myocardial ischaemia during two 2-min coronary artery balloon occlusions with and without simultaneous iCSO by a balloon-tipped catheter. Setting: University Hospital. Patients: 35 patients with chronic stable coronary artery disease. Intervention: 2-min iCSO. Main outcome measures: Myocardial ischaemia as assessed by intracoronary (i.c.) ECG ST shift at 2 min of coronary artery balloon occlusion. Collateral flow index (CFI) without iCSO, that is, the ratio between mean distal coronary occlusive (Poccl ) and mean aortic pressure (Pao ) both minus central venous pressure. Results: I.c. ECG ST segment shift (elevation in all) at the end of the procedure with iCSO versus without iCSO was 1.33±1.25 mV versus 1.85±1.45 mV, p<0.0001. Regression analysis showed that the degree of i.c. ECG ST shift reduction during iCSO was related to CFI, best fitting a Lorentzian function (r 2 =0.61). Ischaemia reduction with iCSO was greatest at a CFI of 0.05–0.20, whereas in the low and high CFI range the effect of iCSO was absent. Conclusions: ICSO reduces myocardial ischaemia in patients with chronic coronary artery disease. Ischaemia reduction by iCSO depends on coronary collateral function. A minimal degree of collateral function is necessary to render iCSO effective. ICSO cannot manifest an effect when collateral function prevents ischaemia in the first place. ClinicalTrials.gov Identifier: NCT01625832.